Scientific computing with multicore and accelerators - Bader, David A. , 1969-; Dongarra, J. J.; Kurzak, Jakub (Chapman & Hall/CRC computational science, 2011)
"The current trend in microprocessor architecture is toward powerful multicore designs in which a node contains several full-featured processing cores, private and shared caches, and memory. The IBM Cell Broadband Engine (B.E.) and Graphics Processing Units (GPUs) are two accelerators that are used for a variety of computations, including signal processing and quantum chemistry. This is the first reference on the use of Cell B.E. and GPUs as accelerators for numerical kernels, algorithms, and computational science and engineering applications. With contributions from leading experts, the book covers a broad range of topics on the increased role of these accelerators in scientific computing".